Procedure-Related Complications of Left Bundle Branch Pacing: A Single-Center Experience - Chen, Xueying; Wei, Lanfang; Bai, Jin; Wang, Wei; Qin, Shengmei; Wang, Jingfeng; Liang, Yixiu; Su, Yangang; Ge, Junbo (Frontiers in Cardiovascular Medicine, 2021)
Abstract Background: Although left bundle branch pacing (LBBP) has emerged as a novel physiological pacing strategy with a low and stable threshold，its safety has not been well documented. In the present study, we included all the patients with procedure-related complications at our centre to estimate these LBBP cases with unique complications. Methods: We enrolled 612 consecutive patients who received the procedure in Zhongshan Hospital, Fudan University, between January 2018 and July 2020. Regular follow-ups were conducted (at 1, 3, and 6 months in the first year and every 6–12 months from the second year), and the clinical data of the patients with complications were collected and analysed. Results: With a mean follow-up period of 12.32 ± 5.21 months, procedure-related complications were observed in 10 patients (1.63%) that included 2 postoperative septum perforations (2/612, 0.33%), 2 postoperative lead dislodgements (2/612, 0.33%), 4 intraoperative septum injuries (4/612, 0.65%), and 2 intraoperative lead fractures (2/612, 0.33%). Pacing parameters were stable during follow-up, and no major complications were observed after lead repositioning in the cases of septum perforation and lead dislodgement. Conclusion: The incidence of procedure-related complications for LBBP, namely postoperative septum perforation, postoperative lead dislodgement, intraoperative septum injury, and intraoperative lead fracture, were low. No adverse clinical outcomes were demonstrated after successful repositioning of the lead and appropriate treatment.